Thermoluminescence of lunar meteorites Yamato-791197 and ALHA-81005 - Sutton, S.R. (1986)
P(論文) The thermoluminescence characteristics of lunar meteorites Yamato-791197 and ALHA81005 are remarkably similar although not identical. Natural TL glow curves peak at a much higher temperature than the artificial glow curves, 350℃ vs. 150℃. The absence of low temperature natural TL is interpreted as resulting from shock heating during lunar ejection. The corresponding shock temperature is estimated to be 470±70℃ (1ms shock time) and the subsequent Earth transit times must have been less than 19000 and 2500 years for Y-791197 and ALHA81005,respectively. The principal difference between the two lunar meteorites is that the pre-ejection TL level of Y-791197 is a factor of 7 greater than that of ALHA81005 indicating that Y-791197 resided at a shallower, more heavily irradiated depth. Irradiation of both objects in the uppermost meters of lunar regolith with a vertical separation of meters would explain the results. departmental bulletin paper